The evolution of the employment in the European Union. A stochastic shift and share approach - Ana Jesús López Menéndez; Matías Mayor Fernández (European Regional Science Association (ERSA), 2002)
The employment is a main economic variable whose evolution has shown different dynamics within the European Union. Recent papers have recovered the significance of the sectoral factors in the explanation of the regional growth. In this sense, shift and share analysis has been considered an extremely useful technique and a standardization procedure has been developed to decompose the regional growth into three components: the national effect, the industry-mix effect and the competitive effect. Although shift and share analysis has been widely used in the explanation of the differences of growth between regions, this method has been criticized since its classical formulation does not allow to test hypotheses. Therefore, stochastic models have been developed as an extension of classical shift and share analysis, allowing the implementation of inferential processes and forecasting tools. The aim of this paper is to analyze the recent evolution of the employment in the European Union, developing a stochastic shift and share model and testing the sources of regional and sectoral differences.
Keywords: 330